Oh ! n’insultez jamais une femme qui tombe !... - Maddalena Bergamin (Revue Italienne d'Etudes Françaises, 2021)
This paper presents an unpublished translation of Victor Hugo’s poem Oh! n’insultez jamais une femme qui tombe!... (1835, Les Chants du crépuscule), followed by a commentary on the semantic and formal choices. The text of the great French novelist and poet was translated according to a general desire of modernization, which led us to make a certain number of non-literal choices. Nevertheless, we have tried to resonate in the Italian text the stylistic vivacity of the original and its remarkable civic character.